2017
DOI: 10.4067/s0717-95022017000401437
|View full text |Cite
|
Sign up to set email alerts
|

Crab Shell Extract Improves Serum Biochemical Markers and Histological Changes of Pancreas in Diabetic Rats

Abstract: MAKALANI, F.; KHAZAEI, M. R.; GHANBARI, E. & KHAZAEI, M.Crab shell extract improves serum biochemical markers and histological changes of pancreas in diabetic rats. Int. J. Morphol., 35(4):1437Morphol., 35(4): -1443Morphol., 35(4): , 2017 SUMMARY: Diabetes mellitus is a common metabolic disease. There are many natural agents available to control and treat diabetes. Crab shell extract has antioxidant properties. The aim of present study was to investigate the effect of crab shell hydroalcoholic extract on blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Additionally, Ramasamy et al, (2014) found that rats treated with chitosan against CCl 4 poisonous quality indicated significantly decreased levels of ALT and AST exercises, total cholesterol, triglyceride and free unsaturated fat in plasma and tissue. These results were according to Makalani et al, (2017) who reported that crab shell expel affected an imperative decline in serum levels of ALT and AST.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Additionally, Ramasamy et al, (2014) found that rats treated with chitosan against CCl 4 poisonous quality indicated significantly decreased levels of ALT and AST exercises, total cholesterol, triglyceride and free unsaturated fat in plasma and tissue. These results were according to Makalani et al, (2017) who reported that crab shell expel affected an imperative decline in serum levels of ALT and AST.…”
Section: Discussionsupporting
confidence: 52%
“…Selenium is a basic piece of the human eating regimen and is found in crab shell (Brozmanová et al, 2010). Likewise, selenium has cell reinforcement and mitigating impacts (Akhuemokhan et al, 2013 andMakalani et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Chitin, chitosan, and their derivatives have important biological properties including antioxidant, anti-inflammatory, antitumor, antimicrobial, and antidiabetic effect, and their antioxidant effects play a vital role in nutrition and human health. [131415]…”
Section: Introductionmentioning
confidence: 99%
“…Various natural compounds with antidiabetic activity are used to control diabetes; our previous studies were shown inhibitory effects of crab shell extract (CSE) on breast cancer cell line (MCF7) and[20] improved pancreatic tissue changes caused by diabetes. [15] The aim of this study was to investigate the effect of CSE on structural changes and ferric-reducing antioxidant power (FRAP) level of renal tissue and urinary biochemical parameters in diabetic rat.…”
Section: Introductionmentioning
confidence: 99%